Effectiveness of Master Program: A case study of Prithivi Narayan Campus, T.U., Pokhara - Baral, Keshar J (Tribhuvan University Journal, 2010)
This paper examines the effectiveness of Master programs run in Prithivi Narayan Campus (PNC) from both financial and academic perspectives. None of the programs is cost effective. Overall, cost recovery rate is very low, and cost of higher education measured in terms of cost per student is relatively high. None of the Master programs excepting the Sociology and Anthropology (will henceforth be mentioned as Sociology) is financially sustainable. Academic performance in terms of pass percent is not satisfactory. Thus, this paper will provide T.U. authority the valuable information for right course of future decision to make the Master programme more effective in its constituent campuses. Key Words: Master programme; Financially sustainable; Prithivi Narayan Campus Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:91-110 Uploaded date: 26, September, 2010